Institutions, public debt and growth in Europe - Klaus Masuch; Edmund Moshammer; Beatrice Pierluigi (European Central Bank (ECB), 2016)
This paper shows that initial cross-country institutional differences can explain to a substantial extent the relative GDP performance of European countries since 1995, after controlling for the initial level of GDP per capita and government debt. It shows that improving the quality of institutions could lead to significantly higher per capita GDP. It also shows that an initial government debt level above a threshold (e.g. 60-70%) coupled with institutional quality below the EU average tends to be associated with particularly poor subsequent real growth performance during this period. Interestingly, the detrimental effect of high debt levels seems cushioned by the presence of very sound institutions. This might be because good institutions help to alleviate the debt problem in various ways, e.g. by ensuring sufficient fiscal consolidation in the longer-run, allowing for better use of government expenditures and promoting sustainable growth, social fairness and more efficient tax administration. The results are confirmed across a large sample of countries, also including OECD countries outside Europe. The empirical findings on the importance of institutions are robust to various measures of output growth, different measures of institutional indicators, different sample sizes, different country groupings and to the inclusion of additional control variables. Overall, the results tend to support the call for structural reforms in general and reforms enhancing the efficiency of public administration and regulation, the rule of law and the fight against rent-seeking and corruption in particular.
Keywords: O43; C23; E02; H63; 330; panel estimates; public debt; public governance; quality of institutions and real growth; structural reforms